Five-year survival rate from triple-negative breast cancer varies on follow up, platin agents and multidisciplinary team: a prospective analysis at tertiary level hospitals in Bangladesh - Khan, Abdullah Al Mamun; Alam, Mohammed Jahangir; Islam, Mohammad Rafiqul; Khurshid, Narita (International Journal of Research in Medical Sciences, 2025)
Background: Triple-Negative Breast Cancer (TNBC) is an aggressive subtype of breast cancer lacking ER, PR, and HER2, with high recurrence and mortality. This study evaluates survival outcomes and treatment impact in Bangladesh. The objective of this study was to assess the five-year survival rate of TNBC patients in Bangladesh, evaluate the impact of platin-based chemotherapy and MDT, and compare the outcomes of neoadjuvant and adjuvant treatments. Methods: This prospective analysis was conducted on 165 TNBC patients from a cohort of 1672 breast cancer patients treated at two tertiary hospitals in Dhaka between January and December 2018. Patient data were collected prospectively, and follow-up was conducted every six months via phone or departmental database. Data on demographic characteristics, co-morbidities, treatment regimens, and survival outcomes were analyzed. Results: Among the 165 TNBC patients, 37 (22.42%) died within the five-year follow-up period, with 52 (58.43%) surviving. Disease-Free Survival (DFS) was observed in 47 (52.81%) patients, and recurrence was recorded in 5 (5.62%). The survival rate varied significantly across different age groups: 59.62% survival in the 40-63 years age group, 32.69% in the 39 and younger group, and 7.70% in the 64 and above group. Notably, 91 (55.15%) patients received neoadjuvant chemotherapy (NACT), and 74.74% of them survived five years. The overall survival (OS) rate was highest in those treated with platinum-based agents, with a survival rate of 70.97%. The median survival time for those receiving MDT was 61.07%, compared to 19.79% for those treated without MDT. A significant correlation was found between treatment completion (p<0.05), chemotherapy regimen (p<0.01), and follow-up adherence (p<0.05) on survival outcomes. Conclusions: This study highlights the importance of early detection, treatment completion, and MDT management in improving TNBC survival, particularly for those under 63 years.